Complex dispersion diagram and evanescent modes in piezomagnetic phononic structures. (15th April 2022) - Miranda, E.J.P.; Rodrigues, S.F.; Dos Santos, J.M.C.
Abstract: The evanescent Bloch waves in Bragg-type band gaps are important for the design of phononic structures with desirable properties. However, the evanescent waves in solid phononic crystals with piezomagnetism have not been reported yet. In this study, it is investigated the complex dispersion diagram of a 2-D piezomagnetic phononic structure. The improved plane wave expansion ( ω ( k ) ) and extended plane wave expansion ( k ( ω ) ) formulations are derived to obtain the propagating and evanescent modes. Full and complete Bragg-type band gaps are observed. The piezomagnetic effect influences significantly the propagating and evanescent modes. The relevant results can be used for the wave attenuation design of smart periodic structures. Highlights: The wave attenuation in a 2-D piezomagnetic phononic crystal is evaluated. Evanescent Bloch waves in a 2-D piezomagnetic phononic crystal are investigated. The piezomagnetism influences the band gap width, the wave attenuation and the wave mode shapes. Piezomagnetic phononic crystals can be useful for wave attenuation design.